Performance Evaluation of Sensor Programming Patterns in SPL of MSRDS - In Chung, Jong (International Journal of Engineering and Technology, 2018)
Background/Objectives: SPL of MSRDS provides many functions for sensor programming. The sensor programming can be implemented in two types of patterns: procedure and while–loop patterns. It is known that the while-loop pattern has better performance than the procedure pattern. Methods/Statistical analysis: To determine if the while-loop pattern has better performance than that of the procedure pattern, we made a simulation environment to evaluate the performance. The simulation environment consisted of a maze and a robot with one of three potential sensors. We measured the required travel time and robot actions (number of turns and number of collisions) needed to escape the maze and compared the performance for the two sensor programming patterns. Findings: We were able to obtain results that showed that the while-loop pattern does not have better performance than the procedure pattern. However, the while-loop pattern is good for making a program that can sense into user’s intent. It is known that programmers prefer the while-loop pattern to the procedure pattern. Improvements/Applications:It is true that for a long time we have adapted the while-loop pattern to simulate sensor programming, without consideration of other methods. Therefore, from now on, it will be convenient to select an easy pattern to use according to the simulation situation because it is now known there is no difference of performance between the two types of sensor programming patterns.